Bile duct ligation–induced biliary hyperplasia, hepatic injury, and fibrosis are reduced in mast cell–deficient KitW‐sh mice. Issue 6 (28th April 2017) - Hargrove, Laura; Kennedy, Lindsey; Demieville, Jennifer; Jones, Hannah; Meng, Fanyin; DeMorrow, Sharon; Karstens, Walker; Madeka, Taronish; Greene, John; Francis, Heather
Abstract : Activated mast cells (MCs) release histamine (HA) and MCs infiltrate the liver following bile duct ligation (BDL), increasing intrahepatic bile duct mass (IBDM) and fibrosis. We evaluated the effects of BDL in MC‐deficient ( Kit W‐sh ) mice. Wild‐type (WT) and Kit W‐sh mice were subjected to sham or BDL for up to 7 days and Kit W‐sh mice were injected with cultured mast cells or 1× phosphate‐buffered saline (PBS) before collecting serum, liver, and cholangiocytes. Liver damage was assessed by hematoxylin and eosin and alanine aminotransferase levels. IBDM was detected by cytokeratin‐19 expression and proliferation by Ki‐67 immunohistochemistry (IHC). Fibrosis was detected by IHC, hydroxyproline content, and by qPCR for fibrotic markers. Hepatic stellate cell (HSC) activation and transforming growth factor‐beta 1 (TGF‐β1) expression/secretion were evaluated. Histidine decarboxylase (HDC) and histamine receptor (HR) expression were detected by qPCR and HA secretion by enzymatic immunoassay. To evaluate vascular cells, von Willebrand factor (vWF) and vascular endothelial growth factor (VEGF)‐C expression were measured. In vitro, cultured HSCs were stimulated with cholangiocyte supernatants and alpha‐smooth muscle actin levels were measured. BDL‐induced liver damage was reduced in BDL Kit W‐sh mice, whereas injection of MCs did not mimic BDL‐induced damage. In BDL Kit W‐sh mice, IBDM, proliferation, HSC activation/fibrosis, and TGF‐β1 expression/secretion were decreased. The HDC/HA/HR axis was ablated in sham and BDL Kit W‐sh mice. vWF and VEGF‐C expression decreased in BDL Kit W‐sh mice. In Kit W‐sh mice injected with MCs, IBDM, proliferation, fibrosis, and vascular cell activation increased. Stimulation with cholangiocyte supernatants from BDL WT or Kit W‐sh mice injected with MCs increased HSC activation, which decreased with supernatants from BDL Kit W‐sh mice. Conclusion : MCs promote hyperplasia, fibrosis, and vascular cell activation. Knockout of MCs decreases BDL‐induced damage. Modulation of MCs may be important in developing therapeutics for cholangiopathies. (Hepatology 2017;65:1991‐2004).